2021
DOI: 10.3389/fpsyg.2021.734703
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Offense at Work and the Impact of Hierarchical Status: The Fault of the Leader, Causal Attributions, and Social Support During the Covid-19 Pandemic Crisis

Abstract: The study explores the mechanism by which unadapted causal attributions and the perception of social support stimulate revenge and reconciliation at the social and professional level in the context of the current pandemic. In particular, the purpose of the study is to investigate the relationship between the accused, the victim and offender status and the search for revenge or reconciliation following a personal offense. To test the suggested research model, we analyzed the data collected by 167 (m = 28.52; SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…It is possible that the occupation (COR), which is a precedent and a causal factor in the perception of social support, is in fact the result of such a conflicting connection. For example, some employees may increase their level of involvement in the profession as a result of low perceptions of family support and as a consequence of loneliness [21,45]. At the same time, it appears that many of the relationships observed in this study are potentially bi-directional.…”
Section: The Negative Aspects Of Social Relationshipsmentioning
confidence: 83%
See 1 more Smart Citation
“…It is possible that the occupation (COR), which is a precedent and a causal factor in the perception of social support, is in fact the result of such a conflicting connection. For example, some employees may increase their level of involvement in the profession as a result of low perceptions of family support and as a consequence of loneliness [21,45]. At the same time, it appears that many of the relationships observed in this study are potentially bi-directional.…”
Section: The Negative Aspects Of Social Relationshipsmentioning
confidence: 83%
“…Alexe et al [20] found that, in the case of performance athletes, perceived social support was not associated with the frequency and severity of daily hassles or negative life events. On the other hand, Marian et al [21] have argued that the orientation towards reconciliation in organizations was more common among employees with high social support while the orientation towards revenge at work was more common among employees with low social support. On the other hand, perceived social support appeared to act as a buffer between the offense perceived by employees and the negative emotions that generated revenge in organizations.…”
Section: Evidence From Studiesmentioning
confidence: 99%